Qualitative Evaluation of Land Suitability for Olive, Potato and Cotton Cultivation in Tarom in Zanjan - Zahra Mirzae Shiri; Manochehr Farbodi (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2022)
The use of soil as one of the main factors in the manufacture of agricultural products for human consumption must be carried out using the right basis and scientific principles. One of the ways to achieve this important goal is to assess land suitability for common crops in the study area. It is also necessary to determine product compatibility based on the soil and climate conditions to reduce the risk of investment because there is no history of the studied plant’s cultivation in the region. Therefore, this study aims to evaluate the suitability of land for cotton, potato, and olive crops at the bottom of the valley in Tadarom in Tarom region, Zanjan province to ensure proper use planning. After sampling and performing physical, chemical, and profile tests using the classification key of 2014, the soils were classified into different Aridi Sols categories, namely Typic calcigypsids, haplocambids, and torriortent. The climate, soil, and terrain data of the area were then collected from the relevant agencies. Land suitability assessment for olive, potato, and cotton was also performed using the simple constraint, parametric, FAO system methods. The evaluation results showed that the Tahdareh area with series 1 soils was in the not suitable (N) and subclass (Ns) categories using the history and second root methods, respectively with depth and pebbles as the limiting factors. Meanwhile, soil series 2, 3, 4, and 5 were placed in the critical fit (S3 ) and proportionality (S2 ) classes by the story and second root methods, respectively, where they were hindered by drainage. Evaluation of these lands for potato crop by story method for series 1, 2 and 3 shows that they were in Ns class, while 4 was in the proportionality (S3 ) category with lime as the limiting factor. The non suitable class was obtained using the story method (N) for series 2, 3, 4 and 5 and they were hindered by soil depth, while class S3 was obtained for all the soils with the texture and gravel as limit factors. The results showed that the studied lands were relatively suitable for olive groves and the conditions can be improved with corrective factors for drainage and the amount of gravel. The storytelling method has very strict output while presenting its results. The study area was considered a land with critical fit (S3 ) class for olive cultivation, but it was not very consistent with field observations. Furthermore, the second root method had the greatest compliance with the existing realities in the region and it can be considered the most reliable parametric technique in the qualitative assessment of land suitability.